Contemporary Issues of the Statistical Evaluation of Price and Volume Measures - Tsvetkov, Stoyan (Research Papers, 2009)
The study is dedicated to some important problems of assessing the differences between the variables, such as economic indicators developed by the contemporary economic statistics. The study discusses mainly practical problems of statistical estimation in the context of the requirements of the European System of Accounts, without having in mind the outstanding theoretical issues in the choice of index formula. It focuses on some of the problems in establishing the price indexes for the deflation and possible solutions, applied by modern statistics, are shown. The survey is intended for professionals in both theory and practice in Economics and Statistics of the Economic System, but can also serve as a teaching tool to students majoring in Statistics and Econometrics and Macroeconomics.